A Analisis Kesesuaian Lahan Tanaman Bawang Merah (Aliium Ascalonicum L.) Menggunakan Metode Fuzzy di Kecamatan Pantai Cermin Kabupaten Solok - Yordani, Ferry Okta (JURNAL BUANA, 2026)
This study was intended to determine (1) the distribution of land suitable for planting shallots in Pantai Cermin Subdistrict, Solok Regency, (2) the area of land that has been utilized and the potential of land for shallot cultivation in Pantai Cermin Subdistrict, Solok Regency. This research uses a quantitative description method with random data sampling. The method used is the Fuzzy method (fuzzification, inference system, and defuzzification) using 9 parameters namely: temperature, rainfall, slope, soil texture, soil depth, soil drainage, soil pH, soil CEC and base saturation. And the land area utilized using SPOT-7 and SAS Planet imagery is analyzed using Supervised with the Maximum Likehood method. (1) The extent of Shallot Land Suitability is: "Very Suitable" 942.17 Ha, "Moderately Suitable" 5988.81 Ha and "Unsuitable" 16178.13 Ha. (2) The area of shallot plantation that has been identified is 220.89 Ha, and currently 148.79 Ha has been used for settlements. The potential of shallot crop land is "Highly Potential" covering 809.06 Ha, "Moderately Potential" covering 5761.60 Ha, "Not Potential" covering 16170.68 Ha. Land utilized (very suitable) with an area of 133.09 Ha, land utilized (moderately suitable) with an area of 227.21 Ha, and land utilized (unsuitable) with an area of 7.24 Ha.